Solution Manual of Elementary Mathematics (module 8) - Tay, Choo Chuan; Sakidin, Hamzah; Othman, Zuraini (Penerbit Universiti, UTeM, 2008)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding.